Pengaruh Pengasuhan Orang tua dan Kemandirian Terhadap Minat Belajar Siswa Akuntansi dan Keuangan Lembaga di Masa Pandemi COVID-19 - Shanti Nugroho Sulistyowati; Putri Nur Anggraini (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2022)
The purpose of this study was to measure and determine the effect of parenting and independence on interest in studying accounting and institutional finance during the COVID-19 pandemic. Quantitative research design with multiple linear regression tests The population of this research is students of accounting and institutional finance expertise at Bisri Syansuri Jombang Vocational School in the academic year 2021–2022, with a sample of 41 students. Saturated sampling is a method used to obtain data. Primary data in the form of interviews and questionnaires given to respondents and secondary data in the form of parental consent documented in the face-to-face learning process, including improving student learning outcomes. Validity and reliability are used to test the prerequisites. Descriptive statistical analysis and classical hypothesis testing were used in the data analysis, which included normality tests, multicollinearity tests, heteroscedasticity tests, autocorrelation tests, and multiple linear regression analyses, which included partial tests, simultaneous tests, and coefficient of determination tests. Based on the findings, 1) parental care has a major effect on interest in learning. 2) Independence has a big effect on an interest in learning. 3) Parenting and parental independence have a significant impact on children's interest in learning.